A Prospective Observational Registry of Repository Corticotropin Injection (Acthar® Gel) for the Treatment of Multiple Sclerosis Relapse - Kaplan, Jeffrey; Miller, Tamara; Baker, Matthew; Due, Bryan; Zhao, Enxu (Frontiers in Neurology, 2020)
Background and Purpose: Effective relapse treatment is critical for minimizing disability in patients with multiple sclerosis (MS). Repository corticotropin injection (RCI; Acthar® Gel) has demonstrated efficacy for the treatment MS exacerbations. However, there is limited real-world evidence available regarding the relationship between the use of RCI for MS relapses and patient demographics, disease characteristics, and dosing regimens. In this multicenter, prospective, observational registry, patients receiving RCI for acute MS relapse were characterized, and recovery and safety outcomes were described. Methods: Patients were invited by their treating clinician to participate in the registry during a routine care visit. The decision to initiate RCI occurred before determination of study eligibility. All treatment decisions were made at the discretion of the patient’s health care provider and were not mandated by the study design or protocol. Each enrolled patient was followed for up to 24 months or until the date of study termination. The primary endpoint was the change from baseline in MS Impact Scale Version 1 (MSIS-29v1) physical subscale scores at month 2. Additional assessments included the MSIS-29v1 psychological subscale, Expanded Disability Status Scale (EDSS), Clinical Global Impression of Improvement (CGI-I), Work Productivity and Activity Impairment Questionnaire: MS (WPAI:MS), and Health Resource Utilization questionnaire. Results: Of 145 patients enrolled, 82 (56.6%) completed 24 months of follow-up. Mean MSIS-29v1 physical subscale scores improved at 2 months (−8.0; P=0.0002) and 6 months (−9.6; P<0.0001). Mean MSIS-29v1 psychological subscale scores also improved at 2 months (−7.9; P=0.0040) and 6 months (−9.9; P=0.0012). Mean EDSS scores improved at 2 months (−0.4; P<0.0001) and 6 months (−0.5; P<0.0001). CGI-I scores indicated improvement in 63.4% of 71 patients at 2 months and 61.4% of 57 patients at 6 months (both P<0.0001). Improvements on the WPAI:MS activity impairment domain (P<0.001) and reductions in outpatient, specialist, and emergency department visits were observed at 2 and 6 months. A total of 35 (28.0%) patients reported 83 adverse events; 11 (8.8%) patients reported 16 serious adverse events. Conclusions: This observational study found significant improvements in MS assessment scores after RCI treatment and supports the efficacy and tolerability of RCI for MS relapse.